Life as Experienced Within and Through the Body After the Age of 85 Years: A Metasynthesis of Primary Phenomenological Research. (May 2020) - van Rhyn, Brianne; Barwick, Alex; Donelly, Michelle
The body is central to the experience of aging. In this metasynthesis, the authors located, analyzed, and reconceptualized phenomenological research on how life is experienced within and through the body after 85 years. Sandelowski and Barroso's metasynthesis method was employed. Seven databases were searched for primary phenomenological studies. After systematic screening and quality appraisal, 19 studies were included for review. Analysis was guided by Maurice Merleau-Ponty's existential philosophy of embodiment. Findings were organized using Max van Manen's reflective lifeworld existentials. Four ontological dimensions emerged, namely, being in a body (corporeality), being in time (temporality), being in place (spatiality), and being with others (relationality). Each dimension captures a distinct experiential dimension of this stage of the life course. The results suggest vast heterogeneity in the ontological experience of aging, supporting the view that diversity grows with age. The ability to adapt to multidimensional losses was identified as a source of resilience.